Ethanol Production Yield from Cassava Mill Effluent using Starch Hydrolyzing Bacterium (Bacillus species) and Glucose Fermenting Yeast (Saccharomyces species) - L. P. Peekate; L. O. Amadi; E. Amos (Journal of Applied Sciences and Environmental Management)
Ethanol yield (EY) from carbohydrate fermentation can be affected by microorganisms involved in the fermentation. Hence, the objective of this paper was to evaluate the ethanol production yield from cassava mill effluent (CME) using a starch hydrolyzing bacterium (Bacillus species) and a glucose fermenting yeast (Saccharomyces species) with high starch hydrolyzing and glucose fermenting potential using appropriate standard methods. The results obtained revealed that the bacterium with the highest zone of clearance on Starch-Nutrient Agar was Bacillus infantis, and the yeast with the highest glucose fermenting potential was Saccharomyces cerevisiae. About 50 % reduction in the population of Bacillus infantis and Saccharomyces cerevisiae occurred beyond 15 % and 25 % ethanol concentration respectively. The highest ethanol concentration (17.2±0.7 %) and yield (47.65±1.92 %) was in CME fermented with Bacillus-Saccharomyces inocula (BSI) ratio of 1:2. However, statistical analysis revealed that there was no significant difference (p = 0.135) in the results obtained with the different inocula ratios. There was pH reduction to slightly acidic after fermentation of the CME, and drastic reduction in cyanide concentration by about 99 %. It is concluded that appreciable EY can be obtained from fermentation of CME using Bacillus infantis and Saccharomyces cerevisiae.